Flavor release from traditional dry-cured pork during oral processing - Xing Tian; Zongjun Li; Ke Li; Zhongqin Wu; Rui Ren; Haodong Wang; Chaoqun Zeng (Food Science and Human Wellness)
The rate of flavor release in the mouth from traditional dry-cured pork was evaluated in this study. It was hypothesized that a slow steady release of flavor would occur on chewing and hydration. To test this, high salt dry-cured pork was chewed and held in oral cavity without swallowing for 4 different chewing stages (B, NC30, C30, EC). Saliva and food bolus from 16 healthy subjects were collected during oral processing, and analyzed for saliva flow rate, total saliva protein content, saliva pH, conductivity, saliva and sodium, and taste components. Results show that oral processing behavior and salivary release have important effects on flavor release of dry-cured pork. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) analysis showed that oral processing has a certain effect on the protein composition and concentration in saliva. This study suggests that the interaction between food and saliva that accompanies chewing can lead to significant changes in sensory perception during oral processing.